Complications of closing wedge high tibial osteotomies for unicompartmental osteoarthritis of the knee. Issue 9 (September 2012) - Atrey, A.; Morison, Z.; Tosounidis, T.; Tunggal, J.; Waddell, J. P.
Abstract : We systematically reviewed the published literature on the complications of closing wedge high tibial osteotomy for the treatment of unicompartmental osteoarthritis of the knee. Publications were identified using the Cochrane Library, MEDLINE, EMBASE and CINAHL databases up to February 2012. We assessed randomised (RCTs), controlled group clinical (CCTs) trials, case series in publications associated with closing wedge osteotomy of the tibia in patients with osteoarthritis of the knee and finally a Cochrane review. Many of these trials included comparative studies (opening wedge versus closing wedge) and there was heterogeneity in the studies that prevented pooling of the results.